Francisco R. De Goenaga y Olza - Astol, Eugenio (My University, 1937)
El artículo de Puerto Rico Ilustrado brinda datos biográficos de Francisco R. De Goenaga y Olza.
Keywords: De Goenaga y Olza, Francisco R., 1850-1913